Multiplex CRISPR/Cas9-mediated raffinose synthase gene editing reduces raffinose family oligosaccharides in soybean - Cao, Li; Wang, Zeru; Ma, Hongyu; Liu, Tengfei; Ji, Jing; Duan, Kaixuan (Frontiers in Plant Science, 2022)
Soybean [Glycine max (L.) Merr.] is an important economic crop in the world, rich in oil, protein, starch and soluble carbohydrate in seeds for human and livestock consumption. The predominant soluble carbohydrate of soybean is comprised of sucrose and raffinose family of oligosaccharides (RFOs). Of these carbohydrates, only sucrose can be digested by human and monogastric animals and is beneficial for metabolizable energy. While RFOs are anti-nutritional factors in diets, usually leading to flatulence, indigestion, ultimately reducing energy efficiency. Hence, breeding efforts to remove RFOs from soybean can increase the metabolizable energy and improve the nutritional quality. In this study, we utilized multiplex CRISPR/Cas9‐mediated gene editing system to induce knockout of soybean raffinose synthesis (RS) genes RS2 and RS3 simultaneously to reduce RFOs in mature seed. First, we constructed five types of multiplex gene editing system in soybean and compared their editing efficiency. We confirmed that two component transcriptional unit (TCTU) and single transcriptional unit (STU) system with tRNA as cleavage site performed better than other systems. The average editing efficiency of four targets with TCTU-tRNA and STU-tRNA was up to 50.5% and 46.7%, respectively. Then we designed four sgRNA targets to induce mutations of RS2 and RS3 by using TCTU-tRNA system. After soybean transformation we obtained several RS2 and RS3 mutation lines and a subset of alleles was successfully transferred to progeny. We identified null single and double mutants at T2 generation and analyzed their progeny seed carbohydrate content. RS2 and RS3 double mutant and RS2 single mutant exhibited dramatically reduced levels of raffinose and stachyose in mature seed. Further analysis for growth and development of these mutant lines showed that there were no penalties on these phenotypes. Our results indicate that knocking out RS genes by multiplex CRISPR/Cas9-mediated gene editing is an efficient way to reduce RFOs of soybean. We believe this will produce great value for metabolizable component of the soybean meal by using more elite soybean cultivars.